ChemInform Abstract: Catalytic Asymmetric Diels—Alder Reaction of Quinone Imine Ketals: A Site‐Divergent Approach. Issue 32 (August 2015) - Hashimoto, Takuya; Nakatsu, Hiroki; Maruoka, Keiji
Abstract The site selectivity in these asymmetric quinone Diels—Alder reactions strongly depends on the structure of the axially chiral dicarboxylic acid catalyst.